T-Symmetry in String Geometry Theory - Matsuo Sato; Taiki Tohshima (Advances in High Energy Physics)
String geometry theory is one of the candidates of nonperturbative formulation of string theory. In this paper, we have shown that dimensionally reduced string geometry theories have what we call T-symmetry. In the case of the dimensional reduction in space-like directions, the T-symmetry transformation gives the T-dual transformation between the Type IIA and IIB perturbative vacua. In the case of the dimensional reduction in the direction of string geometry time τ¯, the T-symmetry transformation is independent of the T-dual transformation and gives a symmetry that cannot be seen in the perturbative string theories.